HUBUNGAN PAPARAN DEBU KAPUR DENGAN STATUS FAAL PARU PADA PEKERJA GAMPING - Erka Dewi Armaeni; Noeroel Widajati (The Indonesian Journal of Occupational Safety and Health, 2016)
The burning of limestone has effects against the labors such as pulmonary function disorders which are acute and chronic. The Pulmonary function disorders which are acute, for example respiratory tract irritation, increased production of mucus, respiratory tract constriction, loss of cilia and mucous membrane cells layer and breathing difficulties. This study was conducted to analyze the strong correlation among the characteristics of the respondent, the respondent habits, level of dust to pulmonary function disorders of the Labors at CV. SRI MULYA PUTRA Tuban. This study uses a cross-sectional study with a quantitative approach. Samples were taken from the study population by 78 people who were previously given initial questionnaire and obtained 23 respondents based on inclusion criteria as the study sample. The independent variables were the characteristics of respondents such as age, sex, length of employment, length of employment, respiratory protective equipment usage habits and exercise habits. The prevalence of respiratory disorder in this study amounted to 13.00%. Test using analysis Contingency Coefficient. The duration of the work is a strong variable to cause pulmonary function disorder to the industrial workforce limestone. The conclusion is there is no strong correlation between the level of limestone dust with pulmonary function status on limestone labor, because the concentration of dust in the working environment is normal, under NAB predetermined. It is advisable to add a work shift, from 2 shifts recommended to be added into 3 shifts. Applying rotation system and providing better respiratory protective equipment.Keywords: limestone dust, pulmonary function status, limestone labor